QSAR and docking based lead optimization of nitrogen heterocycles for enhanced prostaglandin EP2 receptor agonistic potency - Jawarkar, Rahul D; Zaki, Magdi E A; Al-Hussain, Sami A; Samad, Abdul; Long, Chiau Ming *; Rashid, Summya; Elossaily, Gehan M.; Yadav, Susmita; Mali, Suraj (Elsevier, 2024)
In the existing effort, a dataset of 309 experimentally screened molecules for in vitro (Ki) agonist potential for Prostaglandin E2 (PGE2) receptor 2 subtype (EP2), which is a metabolite of arachidonic acid that binds with and regulates cellular responses to PGE2, was investigated in the QSAR (Quantitative structure–activity relationship) study. A six-parameter QSAR model was developed that meets the specified values ​​for internal and external validation as well as random parameters such as R2tr = 0.808, Q2LMO = 0.794, R2ex = 0.781. Insightful and quantitative opinion reveals several underappreciated and distinct structural features that are responsible for the agonist potency of these molecules on Prostaglandin EP2 receptor such as; the hydrogen atom is correct 2 bonds from the donor atom, the sp2 hybridized carbon atom is correct 2 bonds from the cyclic nitrogen atom, and so on. The developed QSAR model captures the narrative as well as the novel pharmacophoric features. The QSAR effect was further demonstrated using the reported crystalline buildings of CP533536 with the Prostaglandin EP2 receptor activity. The evaluation led to the identification of valuable new pharmacophoric properties that will be used to optimize lead compounds in the future.